Marginals Topics: Four Cuban Women Poets from the Eightie´s Generation - autor, Sin (Anales de Literatura Hispanoamericana, 2009)
Through the XX Century, during the decade of the eighties, in Cuba, a series of new voices appear within the literary panorama of young poets born in the first decade posterior to the triumph of the revolution in 1959, and who were educated under its ideological teachings. Added to such a group, we find a group of women poets who began to publish their works without apparent exclusions of the variable sex/genre, like it used to happen in previous years. To unmask such appearances and the continuous sentiment of exclusion that can be traced in these texts is the objective of this work.